Sustainable composites for aerospace applications - Hameed Sultan, Mohamed Thariq (Elsevier, 2018)
Sustainable Composites for Aerospace Applications presents innovative advances in the fabrication, characterization and applications of LDH polymer nanocomposites. It covers fundamental structural and chemical knowledge and explores various properties and characterization techniques, including microscopic, spectroscopic and mechanical behaviors. Users will find a strong focus on the potential applications of LDH polymer nanocomposites, such as in energy, electronics, electromagnetic shielding, biomedical, agricultural, food packaging and water purification functions. This book provides comprehensive coverage of cutting-edge research in the field of LDH polymer nanocomposites and future applications, and is an essential read for all academics, researchers, engineers and students working in this area.